Dramatic Shifts: Interpreting Morocco’s Diplomatic Alteration towards Israel through the Eyes of Defensive Realism - Alfarisi, Habib (Papua Journal of Diplomacy and International Relations, 2024)
Abraham Accord, which took place in December 2020, marks a dramatic shift in the Middle East and North Africa region. Several Arab states, such as Morocco, the UAE, Bahrain, and Sudan, got involved in the pacification process to establish diplomatic relations with Israel. America supported this accord as the ally of Israel in the region. This is because the Arab states that got involved in the accord persistently resisted Israel and supported Palestine to be free. One of the countries that is involved is Morocco. Located in the Northern-Western part of Africa, Morocco faces many external and internal challenges. This, in fact, puts Morocco's position in constant danger. Not confined to problems related to water scarcity, climate change, and underdeveloped agricultural sectors, Morocco also faces the growing threat of Algeria. In addition, Morocco's relations with France also deteriorate due to the scandals of using espionage software. This, in turn, left Morocco with the difficult decision which led to its eventual participation in the accord. In the paper, I analyze why Morocco normalized its diplomatic relations with Israel using the defensive-realist arguments provided by Mearsheimer. Mearsheimer argues that countries utilize power for the sake of their survival. Hence, I hold a view that Morocco's participation in the accord is to neutralize the threats it is facing for the sake of its survival. This paper uses the qualitative method. Keywords: Abraham Accord, Morocco, Defensive-Realism, Dramatic Shift, Diplomatic Relations